Analysis of The Development Strategy for The Bouquet Crafts Business Using the Ansoff Matrix Approach - Darmawan, Muhammad Yusuf; Jazuli, A Muhamad (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – This study aims to formulate business development strategies for Crocho Craft, a bouquet craft business in Malang Regency, to overcome sales fluctuations and support sustainable business growth in the creative craft industry. Design/Methodology/Approach – This study employs a qualitative research method with a development research approach. Data were collected through field studies and literature reviews. The research object is Crocho Craft, a business offering various bouquet products, including fresh flower bouquets, artificial bouquets, snack bouquets, money bouquets, and twisted wire bouquets. Business development strategies were formulated using the Ansoff Matrix framework, covering market penetration, market development, product development, and diversification strategies. Findings – The results indicate that Crocho Craft can improve competitiveness and business sustainability through several strategic initiatives. The proposed strategies include optimizing social media marketing and establishing customer loyalty groups for market penetration, collaborating with Shopee e-commerce for market development, introducing succulent and thematic bouquet variants for product development, and offering table flower products for café and restaurant segments as a diversification strategy. These strategies provide potential solutions to increase market reach, strengthen customer relationships, and reduce sales fluctuations. Originality/Value: This research provides value by applying the Ansoff Matrix specifically to a bouquet craft business, offering a structured strategic model rarely explored in this sector. The study generates practical and context-specific insights that can guide other small creative enterprises in enhancing competitiveness and mitigating sales fluctuations.